2000
DOI: 10.1128/jvi.74.22.10714-10728.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Bovine Respiratory Syncytial Virus

Abstract: Until now, the analysis of the genetic diversity of bovine respiratory syncytial virus (BRSV) has been based on small numbers of field isolates. In this report, we determined the nucleotide and deduced amino acid sequences of regions of the nucleoprotein (N protein), fusion protein (F protein), and glycoprotein (G protein) of 54 European and North American isolates and compared them with the sequences of 33 isolates of BRSV obtained from the databases, together with those of 2 human respiratory syncytial virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
0
13

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(182 citation statements)
references
References 76 publications
5
164
0
13
Order By: Relevance
“…Similar types of change have been described for the G gene of other members of the subfamily Pneumovirinae; use of alternative transcription termination codons has been described for BRSV (Furze et al, 1997) and HRSV (Sullender et al, 1991;Peret et al, 1998;Martinez et al, 1999), and in-frame and frame-shift insertions have been identified with HRSV (Sullender et al, 1991;Peret et al, 1998). Like APV, HRSV and BRSV (Johnson et al, 1987;Juhasz et al, 1994;Bäyon-Auboyer et al, 2000;Valarcher et al, 2000), the nucleotide substitutions resulted in a higher rate of amino acid changes, especially in the ectodomain. This suggests amino acid changes are advantageous, possibly due to immunological pressure.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar types of change have been described for the G gene of other members of the subfamily Pneumovirinae; use of alternative transcription termination codons has been described for BRSV (Furze et al, 1997) and HRSV (Sullender et al, 1991;Peret et al, 1998;Martinez et al, 1999), and in-frame and frame-shift insertions have been identified with HRSV (Sullender et al, 1991;Peret et al, 1998). Like APV, HRSV and BRSV (Johnson et al, 1987;Juhasz et al, 1994;Bäyon-Auboyer et al, 2000;Valarcher et al, 2000), the nucleotide substitutions resulted in a higher rate of amino acid changes, especially in the ectodomain. This suggests amino acid changes are advantageous, possibly due to immunological pressure.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have identified conserved clusters of cysteine residues in the G glycoprotein of HRSV (reviewed by Collins et al 2001), APV (Bäyon-Auboyer et al 2000;Alvarez et al, 2003) and BRSV (Furze et al, 1997;Elvander et al, 1998;Valarcher et al 2000), although BRSV G gene isolates lacking the central four cysteine residues have been described (Valarcher et al, 2000). Cystine nooses have been associated with protein conformation and biological signalling (Lapthorn et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the changes are localized in two regions of the gene, representing the mucin-like regions, those changes have the character of nonsynonymous one-point mutations. On the contrary, the central hydrophobic region is more stable with prevailing synonymous mutations (Valarcher et al, 2000). Single nucleotide sequences differ in onepoint substitutions.…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…These mutant viruses were stable in further nonselective passages and grew with unchanged intensity in a mixed viral culture with the original virus. In addition, Valarcher and others (Valarcher et al, 2000) isolated viruses from diseased animals that had all four cystein residues replaced by arginine. Those substitutions led to structural changes in the central conserved region with the disturbance of α helix Cys 173-Cys 176.…”
Section: G Protein Structurementioning
confidence: 99%
See 1 more Smart Citation